Evolusi Strategi Politik Joko Widodo dalam Lima Kontestasi Elektoral di Indonesia: Dari Pilkada Solo hingga Pengaruh pada Pilpres 2024 - Khoirun Nikmah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
This article analyzes Joko Widodo’s (Jokowi) political strategies across five electoral contests in Indonesia from 2005 to 2024. The study employs a qualitative approach using a literature review method to examine patterns of political communication, campaign strategy, and power consolidation undertaken by Jokowi. It uses an integrative theoretical framework that combines populism theory, political communication theory, and coalition theory as analytical tools. The findings indicate that Jokowi’s dialogic, egalitarian, and people-oriented leadership style served as the primary foundation of his electoral success. He relied on strategies such as blusukan (impromptu visits to communities), social media use, and program-based campaigns focused on pro-people policies, including the restructuring of street vendors, the Jakarta Health Card (Kartu Jakarta Sehat), and the Jakarta Smart Card (Kartu Jakarta Pintar). Party consolidation and broad coalition-building further strengthened his political base, supported by digital volunteers and millennial groups. In the 2014 and 2019 presidential elections, Jokowi capitalized on his image of simplicity, closeness to the people, and endorsements from influential figures such as Jusuf Kalla and Ma’ruf Amin. Approaching the 2024 election, Jokowi’s political influence remained significant despite his not running for office, with the so-called “Jokowi effect” playing a role in shaping voter support. This study argues that Jokowi’s success should not be understood merely as a combination of leadership style and campaign techniques, but as a systematic integration of populist appeal, adaptive political communication, and pragmatic coalition-building. Theoretically, this research contributes to the development of electoral politics studies in Indonesia by offering an integrative analytical framework for understanding contemporary political leadership. Practically, the findings provide insights for political actors and campaign strategists in designing effective, adaptive, and context-sensitive electoral strategies.